EXPLORING GAMIFICATION ELEMENTS IN EDUCATION: A BIBLIOMETRIC STUDY - Nor Zaitul Shahira Zakaria; Hanifah Mahat, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This bibliometric study examines the integration of gamification elements within educational contexts, highlighting trends, influential research, and collaborative networks in the field. Gamification, increasingly recognized for its potential to enhance student engagement and motivation, has become a focal point in educational research. However, there remains a need for a comprehensive analysis to map its development, identify key contributors, and evaluate its impact. This study addresses these gaps by analyzing 1,637 documents from the Scopus database, focusing on publications related to gamification in education. Methodologically, Scopus Analyzer was used to identify publication trends, while VOSviewer software facilitated keyword mapping and co-authorship network analysis. The results reveal a steady increase in research activity, particularly since 2020, reflecting a growing acceptance of gamification as a viable educational tool. Key findings reveal that "gamification," "engagement," and "motivation" are frequently occurring keywords, indicating core themes within the field. The United States, Spain, and the United Kingdom emerged as the leading contributors in terms of publications and collaborations, highlighting significant international interest. Additionally, prominent authors have contributed substantially to advancing theoretical and practical knowledge on gamification's application in diverse educational settings. Despite this progress, gaps remain in standardized frameworks and longitudinal studies assessing gamification's long-term impact. In conclusion, the study underscores the extensive research interest in gamification within education, its established benefits, and the collaborative efforts across countries. Thus, future research should focus on addressing identified gaps by developing structured frameworks and conducting studies that evaluate the sustained effectiveness of gamified interventions across various educational contexts. This bibliometric analysis provides a foundation for educators, researchers, and policymakers to understand the evolving landscape of gamification in education.